2008
DOI: 10.2118/102727-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Oil Viscosity on Oil/Gas Flow Behavior in Horizontal Pipes

Abstract: Summary Oil/gas pipe flows are expected to exhibit significantly different behavior at high oil viscosities. Effects of high-viscosity oil on flow pattern, pressure gradient, and liquid holdup are experimentally observed, and differences in flow behavior of high- and low-viscosity oils are identified. The experiments are performed on a flow loop with a test section of 50.8-mm ID and 18.9-m-long horizontal pipe. Superficial liquid and gas velocities vary from 0.01 to 1.75 m/s and from 0.1 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 15 publications
7
40
1
Order By: Relevance
“…Figure 4 shows the results for our model flow regime predictions for air-medium viscosity oil ( ϭ 36 cP) and air-high viscosity oil ( ϭ 587 cP) systems. The results have been compared with the experimental data from Brito et al (2013) for the medium viscosity oil system and Gokcal et al (2005) for the high viscosity oil system. The results were also compared with other theoretical models as shown in the figure.…”
Section: Validation Of Flow Regime Map Predictionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 4 shows the results for our model flow regime predictions for air-medium viscosity oil ( ϭ 36 cP) and air-high viscosity oil ( ϭ 587 cP) systems. The results have been compared with the experimental data from Brito et al (2013) for the medium viscosity oil system and Gokcal et al (2005) for the high viscosity oil system. The results were also compared with other theoretical models as shown in the figure.…”
Section: Validation Of Flow Regime Map Predictionsmentioning
confidence: 98%
“…Tulsa (Meng, 1999) 153 Manabe 2001 Natural gas-crude oil 2 Univ. Tulsa (Manabe, 2001) 247 Mata et al 2002 Air-oil (ϭ 0.480 cP) 2 Intevep, Venezuela (Mata et al, 2002) 8 0 Abduvayt et al 2003 Nitrogen-water 2, 4 Waseda Univ., Japan (Abduvayt et al, 2003) 443 Gokcal et al 2005 Air-oil (ϭ 0.181-0.587 cP) 2 Univ. Tulsa (Gokcal, 2005) 183 Brito et al 2012 Air-oil (ϭ39-166 cP) 2 Univ.…”
Section: Mandhane 1974mentioning
confidence: 99%
“…The first experimental study at Tulsa University Fluid Flow Projects (TUFFP) on high viscosity oil was completed by Gokcal (2005). The effects of high oil viscosity on oil-gas two-phase flow behavior were investigated and significant changes in flow behavior were observed.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation may be the reduction on the surface tension of the liquid phase (Water has almost three times the oil surface tension). According to previous studies the effect of the liquid viscosity was found to be negligible over the stratified to annular flow transition (See Gokcal et al (2008); Weisman et al (1979)). According to previous studies the effect of the liquid viscosity was found to be negligible over the stratified to annular flow transition (See Gokcal et al (2008); Weisman et al (1979)).…”
Section: Flow Mapsmentioning
confidence: 80%